Comorbilidades y uso previo de antibióticos en pacientes adultos hospitalizados con infección por Acinetobacter sp. resistente a carbapenems - Castro Apolinario, Darly Mercedes (2020)
Objective: The objective was to determine the frequency of comorbidities and the previous use of antibiotics in adult patients hospitalized with Acinetobacter sp. resistant to carbapenems. Material and methods: Observational and descriptive study, in adult patients hospitalized with Acinetobacter sp infection in the internal medicine service and ICU of the Regional Teaching Hospital of Trujillo during the 2011-2017 period; The frequency of comorbidities (diabetes mellitus, arterial hypertension and chronic kidney disease) and the previous use of antibiotics (carbapenems, aminoglycosides, quinolones, 3rd and 2nd generation cephalosporins, vancomycin, metronidazole and ampicillin-sulbactam) were determined in these patients and then, their association was analyzed using chi-square. Results: The sample was 33 patients; where A. baumannii was the only species found, with 30 resistant strains and 3 susceptible to carbapenems. The majority were males (63.6%), an average age of 53.5 ± 6.9 years was obtained and only a significant difference was evidenced for the previous use of carbapenems (p = 0.036). Conclusion: The majority presented at least one comorbidity and previously used at least one antibiotic; mainly in the group with infection with ABRC.